Uma análise da educação feminina em o Livro das Tres Vertudes a Insinança das Damas de Christine de Pizan - Lima, Gizelda Ferreira do Nascimento (2019)
This research of the study the Book of Three Vertudes (1405), of the author Christine de Pizan from a perspective compared to other study period , among them, Institutione Feminae Christianae (1524) of Juan Luís Vives, The Perfect Married (1583) by Fray Luis de León, Lo Libre de les Donas (1542) of Francisco Eiximenis and the Llibre de les dones or Spill (1460) of Jaume Roig. The corpus of our work is the Portuguese translation of the Pizan entitled, The Book of Three Vertudes the Insanity of the Damas, published around of 1450 at the request of Queen D. Isabel. It is a text intended exclusively for the education of women, its content is composed of teachings and advice from practical order that say a lot about the rules imposed on women in the Middle Ages. Inserted in a tradition of writings formed mostly by male authors, Pizan builds its education project based on strategies that differentiate them from other treaties of education. Thus, we will seek to defend how the author issue differentiated treatment and teaching for women in this context. For this, we use as theoretical support the works of Crispim (2002), Leite (2015), Deplagne (2006), Fernandes (1995), as well as other studies on education treaties for women in the medieval period.